2012
DOI: 10.1177/0020872812452177
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the risk factors that contribute to child labor in Turkey: Implications for research, policy, and practice

Abstract: Child labor is a serious issue in Turkey. This article provides a review of the current literature on risk factors associated with child labor in Turkey. Emphasizing their multilayered nature, the article examines risk factors contributing to child labor in Turkey by clustering them under individual, family, and structural factors. Recommendations for future research, policy, and practice are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Similarly, sometimes the demographic factors such as locality, geographical area and ecological condition forces children to work. Bahar (2014) argued that though children work both in rural and urban areas, but the percent of children are more in rural areas particularly in agriculture in comparison to urban areas. Kothari (1983) in her study on the match stick industry in Sivakasi, Tamil Nadu found that children were forced to leave school to support the family economy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sometimes the demographic factors such as locality, geographical area and ecological condition forces children to work. Bahar (2014) argued that though children work both in rural and urban areas, but the percent of children are more in rural areas particularly in agriculture in comparison to urban areas. Kothari (1983) in her study on the match stick industry in Sivakasi, Tamil Nadu found that children were forced to leave school to support the family economy.…”
Section: Introductionmentioning
confidence: 99%